Global driving forces shaping the future of the Finnish cadastral system by 2035 : a Delphi study - Zavialova, Sofia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
Sustainable and efficient land management system is a crucial factor for the well-being of every society. Cadastral system as a constituent of land management system plays an important role in ensuring legality of relationships between land and its owners, government and citizens. Cadastre is a storage of information regarding who owns the land, its boundaries and rights of its owner. However, this system has evolved along with the macro transformations in human society. Such macro phenomena as industrialization, urbanization, emergence of real estate market, and technological advancements influenced on the operational environment of the cadastral system considerably. If the external environment changes, all the subsystems inside it have to transform as well in order to remain relevant and be convenient for its users. The aim of this thesis was to understand future operational environment of the cadastral system in Finland towards 2035. The study intended to answer two research questions: (1) What are the global drivers shaping the operational environment of the cadastral system in Finland by 2035? (2) What are the alternative scenarios of the operational environment of the cadastral system in Finland? Contextually and conceptually, this study lies between two scientific domains, cadastral research and futures studies. The research strategy was designed following the principle of a well-established futures studies method, Disaggregative Policy Delphi. The study was conducted from October 2016 until January 2017. Experts from various fields related to land management and land use were invited to estimate probable and preferred impacts of the listed megatrends on the development of the cadastral system in Finland. The core part of the questionnaire in both rounds consisted of five step Likert scale questions, however respondents were also asked to support their choice with qualitative arguments. Besides, respondents were invited to estimate relevance of these megatrends to the development of cadastral system. Finally, the most relevant driving forces shaping the operational environment of the cadastral system were identified and four normative scenarios were constructed based on the hierarchical cluster analysis. Findings of the study revealed the relevance of technological phenomena such as digital culture and ubiquitous intelligence and political tendency towards transparency, accessibility and open data to the operational environmental of the Finnish cadastral system. Scenarios analysis reaffirmed these elaborations, i.e. three out of four future visions were driven by mainly technological and economic megatrends, whereas social and environmental ones received lower value.